2022
DOI: 10.5603/gp.a2022.0061
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption during pregnancy — what the gynecologist should know? Review of the literature and clinical studies

Abstract: Coffee is one of the most consumed beverages in the world. The impact of coffee consumption on human health has been the subject of many clinical studies and meta-analyses. Taking into account the results of these studies, it can be concluded that coffee has a number of health benefits in terms of the population, including the reduction of the risk of death from any cause. From a clinical point of view, the safety of coffee consumption in a specific subpopulation of pregnant women is important. A large percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…As far as caffeine use is concerned, our results showed that a high proportion of women (98.6%) consumed caffeine products before conception, which decreased during pregnancy (86.6%) and even more on day 4 postpartum (63.8%), followed by an increase in the first (73.7%), third (79.8%) and sixth (84.8%) month after delivery and after breastfeeding cessation (94.7%). In the US, 80% of pregnant women continue to consume coffee during pregnancy, a prevalence very close to that of our study 33 , while European countries report lower values during pregnancy (France: 47.1%, Italy: 42.3%, Finland: 31%) 34 . Current research on caffeine consumption during breastfeeding focuses mainly on adverse effects on infants 35,36 , rather than on prevalence and maternal outcomes in relation to the extent of breastfeeding exclusivity and duration.…”
Section: Discussionsupporting
confidence: 88%
“…As far as caffeine use is concerned, our results showed that a high proportion of women (98.6%) consumed caffeine products before conception, which decreased during pregnancy (86.6%) and even more on day 4 postpartum (63.8%), followed by an increase in the first (73.7%), third (79.8%) and sixth (84.8%) month after delivery and after breastfeeding cessation (94.7%). In the US, 80% of pregnant women continue to consume coffee during pregnancy, a prevalence very close to that of our study 33 , while European countries report lower values during pregnancy (France: 47.1%, Italy: 42.3%, Finland: 31%) 34 . Current research on caffeine consumption during breastfeeding focuses mainly on adverse effects on infants 35,36 , rather than on prevalence and maternal outcomes in relation to the extent of breastfeeding exclusivity and duration.…”
Section: Discussionsupporting
confidence: 88%
“…According to the recommendations of the American College of Obstetricians and Gynecologists (ACOG), the permissible daily dose of caffeine that is safe for a pregnant woman and her child is ≤200 mg [6]. However, Surma & Witek point out in their research that many women do not give up coffee during pregnancy, and a significant number of women exceed the permissible daily dose of caffeine (≤ 200 mg) [23]. In our study, less than a half of the surveyed women limited the amount of coffee they consumed during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee and tea also have health -promoting properties, including cardioprotective ones. 61, 66 Consuming polyphenols in various food products is an important method of cardiovascular prevention. [67][68][69][70] At this point, it is worth mentioning the "French food paradox" described by Dr Serge Renaud in 1992.…”
Section: Mediterranean Diet and Winementioning
confidence: 99%